INTERAKSI KELAS SEBAGAI FORMASI SPIRITUALITAS PARTISIPATIF - Nindyo Sasongko (P3TK, Sanata Dharma University, 2016)
How does Christian higher education relate to spiritual formation? In this study I will present a broader picture of spirituality of Christian higher education and then layout a spirituality of classroom. I contend that Christian higher education must aim to educate the whole person, and as such, interactions in the classroom is an integral part of this educational-spiritual formation. A classroom must be seen as a space where teacher and students can find God, participate in the divine life, and give space for the others to grow in all dimensions of life. A classroom, therefore, is a space for contemplating the divine presence. To elaborate this topic, I shall, firstly, adumbrate the correlation between spirituality and education. Secondly, as a philosophical grounding of the Christian higher education, I shall discuss the Roman Catholic intellectual tradition and especially the Ignatian tradition which has been contributing to significant developments in the history of higher education. Thirdly, I shall sketch a contextual spirituality of classroom which is inspired by Christian theological tradition, especially that of trinitarian theology.